Bacterial diacetyl suppresses abiotic stress‐induced senescence in Arabidopsis. Issue 6 (21st May 2022) - Singh, Sunil K.; Sun, Yazhou; Yang, Yu; Zuo, Ziwei; Wu, Xiaoxuan; Shao, Chuyang; Peng, Li; Paré, Paul W.; Zhang, Huiming
Summary: Premature plant senescence induced by abiotic stresses is a major cause of agricultural losses worldwide. Tools for suppressing stress‐induced plant senescence are limited. Here, we report that diacetyl, a natural compound emitted by the plant‐beneficial bacterium Bacillus amyloliquefaciens, suppresses abscisic acid ‐mediated foliar senescence in Arabidopsis thaliana under various abiotic stress conditions. Our results establish diacetyl as an effective protector against stress‐induced plant senescence and reveal a molecular mechanism for bacteria‐enhanced plant stress resistance. Abstract : Diacetyl, a natural compound emitted by the plant‐beneficial bacterium Bacillus amyloliquefaciens, suppresses abscisic acid‐mediated foliar senescence in Arabidopsis thaliana under various abiotic stress conditions.